(untitled) - Canter, Rachelle J. (Hoboken, N.J.)
ake the Right Career Move is a wonderful guide for the new age professional. This book will help you execute one of the most important decisions in your life and includes practical tips that you will use for the rest of your career."
Keywords: Career development.,Job hunting